The influence of pandemics in neighborhoods’ public realms: Experts’ point of view in light of social capital - A. Asadpour; H. Nikounam Nezami (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: Neighborhoods’ public realms get their sustainability from the presence of residents but the COVID-19 pandemic restricted the attendance of people. Hence, in light of the social capital paradigm may be revitalized the public realms. Adopting the approach of social capital and its components namely: social interaction, social participation, and spatial equity can improve the socio-physical characteristics of public realms during the outbreak of COVID-19. The extant study was conducted to evaluate the effect of COVID-19 on public realms of neighborhoods from the point of view of architecture and urbanism experts based on the components of social capital. This study aims to achieve strategies for planning and designing public realms by considering the COVID-19 condition, through which public spaces can be promoted in socio-physical dimensions.METHODS: This research was quantitative with an inferential approach. The evaluation of 128 different nation scholars has been analyzed with an inferential approach and exploited LISREL8.8 and SPSS23 for their analysis.FINDINGS: Findings indicate that the indicators of social interaction (Sig. <0.359) and spatial equity (Sig. <0.174) from most experts' views have the same structure and have a significant impact on the public realms of neighborhoods according to the pandemic. Moreover, there is a substantial difference in the social participation (Sig. >0.022) indicators between the two groups of experts.CONCLUSION: Re-programming activity and restructuring physical (social interaction) developing and expanding green and open spaces and physical and functional flexibility (spatial equity) are the most important indicators for promoting public realms.